Globalization, Metropolization, and Urban Change in South Africa - (:unkn) unknown (My University, 2004)
How is metropolization in big cities a consequence of globalization? The present article answers this question in general and then through the South African case, in particular. In South Africa, metropolization is ambiguous. The big cities have had an economic development comparable to that of the so-called rich countries’ cities, those with a strong economic metropolization. The industrial crisis, under the effect of economic globalization, has provoked in South Africa and elsewhere social spatial changes that can be described as processes of "urban fragmentation." But this pattern is disturbed here by the very heavy legacy of the apartheid period. Authorities have implemented a policy of administrative metropolization of the big cities in order to reduce it. Can this manage to slow down or reverse a process of social-spatial fragmentation whose causes are found at a different level? Or is administrative metropolization just a facade that hides the continuation of market-based economic metropolization that leads to the accentuation of fragmentation of the urban organization? If one accepts the polysemy of the term metropolization, one observes that political, economic and territorial metropolizations rarely go hand in hand.
Keywords: African Research